An analytical solution for wave propagation in a square pile due to transient point load. (March 2017) - Qu, Liming; Ding, Xuanming; Zheng, Changjie; Liu, Hanlong
Abstract: This paper presents an analytical solution for wave propagation in a square pile due to transient point load. The differential equation of dynamic equilibrium is established considering propagation of waves in both vertical and transverse directions. The soil resistance is simulated by Voigt model. The three-dimensional analytical solution is deduced by using Fourier transform and the separation of variable method. The arithmetical results of the proposed solution show that the velocity responses along the radial direction at the pile top are highly non-uniform. In addition, Young's modulus and the pile side length exert undisputable influences on the velocity responses.